Red Fluorescent Chlamydia trachomatis Applied to Live Cell Imaging and Screening for Antibacterial Agents - Mojica, Sergio A.; Eriksson, Anna U.; Davis, Rohan A.; Bahnan, Wael; Elofsson, Mikael; Gylfe, Åsa (Frontiers in Microbiology, 2018)
In this study, we describe the application of a transformed Chlamydia trachomatis strain constitutively expressing the red fluorescent protein mCherry, to allow real-time monitoring of the infection cycle and screening for agents that block replication of C. trachomatis. The red fluorescent C. trachomatis strain was detected autonomously without antibody staining and was equally susceptible to doxycycline as the wild type strain. A high throughput-screening assay was developed using the transformed strain and automated fluorescence microscopy. The assay was used in a pilot screen of a 349 compound library containing natural products from Australian flora and fauna. Compounds with anti-chlamydial activity were tested for dose response and toxicity to host cells and two non-toxic compounds had 50 % effective concentration (EC50) values in low micromolar range. Natural products are valuable sources for drug discovery and the identified Chlamydia growth inhibition may be starting points for future drug development. Live cell imaging was used to visualize growth of the red fluorescent C. trachomatis strain over time. The screening assay reduced workload and reagents compared to an assay requiring immunostaining and could further be used to monitor the development of Chlamydia inclusions and anti-chlamydial effect in real time.